The effect of the strategy of removing the strange thing on the achievement of the subject of the history of Arab-Islamic civilization among fourth-grade literary students - Fayyadh, Amjad (Al-Adab Journal, 2025)
Aim of the present research is to find out the strategy of extracting thing strange in the collection of the subject of the history of Islamic Arab civilization among students for fourth grade morality.The research sample was made up of 62 students, who were excluded failing students in Al-Saffa Preparatory School for boys in Baghdad Al-Rsafa first.Depends on the result we obtained:Use of strategy thing strange to collect the subject of the history of Arab-Islamic civilization among students in the fourth grade of morality makes the learning process productive and active, leading to the best scientific output.